ASSOCIATION REPORTS. - Dixon, Robert L. (The Accounting Review, 1946)
The Committee on Cost Accounting Principles has held one meeting and contemplates holding a second meeting before the end of 1946. A basic outline of the cost accounting subject matter has been prepared as a starting point in the search for fundamental principles and the ideas of the committee members have been consolidated through correspondence. The charge of the committee was to explore the feasibility of expressing general principles in the field of cost accounting, and, although the committee is not prepared to report definite conclusions at the present time, it is believed that further exploration will prove fruitful. During the year 1945 a number of manuscripts were given consideration as potential monograph material and it is to be hoped, barring continued shortage of paper and printing labor, that one or more research projects can be published during 1946. A project which has been in process for some time, the preparation of a complete index for the first twenty volumes through 1945 of the journal "The Accounting Review," is now practically complete and printers' bids are being received.